2016
DOI: 10.1021/acscatal.6b00416
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Mild Carbon Dioxide Hydrogenation to Formate Catalyzed by Fe(II) Hydrido Carbonyl Complexes Bearing 2,6-(Diaminopyridyl)diphosphine Pincer Ligands

Abstract: Fe­(II) hydrido carbonyl complexes supported by PNP pincer ligands based on the 2,6-diaminopyridine scaffold were found to promote the catalytic hydrogenation of CO2 and NaHCO3 to formate in protic solvents in the presence of bases, reaching quantitative yields and high TONs under mild reaction conditions, with pressures as low as 8.5 bar and temperatures as low as 25 °C. NMR and DFT studies highlighted the role of dihydrido and hydrido formate complexes in catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
105
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(108 citation statements)
references
References 23 publications
0
105
0
3
Order By: Relevance
“…Although tempting to draw conclusions on mechanism as either inner or outer sphere from this literature comparison, this analysis is arguably complicated by the relative bond dissociation free energies for the differing M–H species. We sought then to compare our values to those for reported iron hydride species , . To our knowledge, no such kinetic study has been reported for an iron hydride complex.…”
Section: Resultsmentioning
confidence: 99%
“…Although tempting to draw conclusions on mechanism as either inner or outer sphere from this literature comparison, this analysis is arguably complicated by the relative bond dissociation free energies for the differing M–H species. We sought then to compare our values to those for reported iron hydride species , . To our knowledge, no such kinetic study has been reported for an iron hydride complex.…”
Section: Resultsmentioning
confidence: 99%
“…[9,10] We and others have previously reported on the hydrogenation of ketones,e sters,a cids, amides,a nd nitriles using catalysts based on earth abundant metals. [11] Recently,P rakash has reported manganese catalyzed conversion of CO 2 to methanol via the formation of formamide in presence of an amine. [11] Recently,P rakash has reported manganese catalyzed conversion of CO 2 to methanol via the formation of formamide in presence of an amine.…”
mentioning
confidence: 99%
“…Under the same catalytic conditions,hydrogenation of diethyl carbonate resulted in the formation of ethanol and methanol in 97 %a nd 95 %y ields,r espectively.D ibenzyl carbonate, diphenyl carbonate,a nd unsymmetrical methyl carbonates ( Table 1, entries [5][6][7][8][9][10][11] were also hydrogenated to afford the corresponding alcohol and methanol in good to excellent yields.W ethen used complex 1 for the hydrogenation of the more challenging cyclic carbonates.U nder the optimized conditions used for the hydrogenation of acyclic carbonates, only 60 %c onversion of propylene carbonate was observed, forming propylene glycol and methanol in % 60 %a nd 45 % yields,r espectively.I ncreasing the hydrogen pressure to 50 bar and reaction time to 48 hr esulted in the quantitative conversion of propylene carbonate to propylene glycol and methanol. Increasing the reaction time to 30 hand the amount of base to 4mol %resulted in approximately quantitative conversion of dimethyl carbonate to methanol, which was detected in 90 % yield by 1 HNMR spectroscopy.Encouraged by this result, we explored the hydrogenation of other types of carbonates.…”
mentioning
confidence: 99%
“…The triplet resonance at − 23.80 ppm shown in Fig. 1 can be assigned to the hydride formate complex A [16]. The major species, however, still remains the pre-catalyst 1 pointing towards incomplete catalyst activation.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous studies [1316] as well as the observations made in the NMR experiment described above, a catalytic cycle has been proposed which is depicted in simplified form in Scheme 2. The pre-catalyst 1 gets activated by replacement of the bromide ligand by the formate anion.…”
Section: Resultsmentioning
confidence: 99%